(untitled) (The Strategic Review for Southern Africa, 2020)
South Africa is a country of global, continental and regional strategic importance. It is a global actor with the well-entrenched and long-standing international political and corporate role and presence and relative global strength. It is Africa’s qualitatively largest and strongest diversified economy. It is African continental and Southern African regional power with considerable continental and regional strength. These factors give it enormous advantages and privileges in playing a leading role in African affairs. They also, dialectically, serve as its key challenges it faces in its efforts to structurally transform its society and to contribute towards structural regional and continental restructuring. How given these factors should South Africa strategically invest on its national security in Southern Africa – the region where it has considerable power and authority – a region whose dependence upon it is a dominated process? There is a fundamental need for this process to be substantially reduced for South Africa’s long-term strategic interests. Its sustainable national security and increased progressive role in African affairs require truly regional allies in a requisite position to come to its aid in a period of its urgent need. Weak regional countries crucially depending on South Africa are of less importance to it. The achievement of their sustainable development is in the long-term strategic interests of South Africa in its internal and external relations. It is not only regional countries which need South Africa for their national security. South Africa also critically needs them particularly as a country expected to substantially increase its leading role in the structural regional and continental transformation. Its sustainable national security lies not only with the majority of its people, based on the satisfaction of their interests, investing on its defence, but also with the structurally restructured region walking together with it in the advancement of the structural continental transformation.